Performance measures and metrics for e‐supply chains - Sambasivan, Murali; Mohamed, Zainal Abidin; Nandan, Tamizarasu (Emerald Group Publishing, 2009)
Purpose: e‐Supply chains are fast becoming a reality. In order to manage such supply chains efficiently and effectively, traditional measures of supply chain performance are not adequate. The literature search revealed lack of measures and metrics for e‐supply chains. The purpose of this paper is to develop new measures and metrics for monitoring the performance of e‐supply chains. Design/methodology/approach: A framework based on the benefits of e‐supply chains has been used to develop the metrics and measures. The study makes use of focus group discussion by assembling eight experts and practitioners in the field of e‐supply chain to come up with the measures and metrics. A questionnaire is designed with these measures and metrics and is sent to about 300 electronic component manufacturing companies in Malaysia to obtain feedback from the industry practitioners. Appropriate reliability and validity tests are conducted to measure the reliability of the instrument and validity of the constructs. Findings: Through the focus group discussion, this study identifies six metrics and 21 measures. Further validation through the industry practitioners, reveals that these measures are important and some are in use by the industries. The six metrics are: web-enabled service, data reliability, time and cost, e-response, invoice presentation and payment and e-document management metrics. Originality/value: The study uses a simple framework and a sound methodology to develop new measures and metrics that are relevant for e‐supply chains.